Pierre Boulez, Music Lessons: the Collège de France Lectures - Boulez, Pierre 1925-2016; Dunsby, Jonathan; Goldman, Jonathan -1972; Whittall, Arnold -1935 (London Faber & Faber, 2018)
Pierre Boulez was appointed to the Collège de France in 1976, with the chair devoted to 'Invention, technique and language in Music', and he held his position until 1995. The publication of his extraordinary Collège de France lectures, his most significant writings from the 1970s to the 1990s, will make a major contribution to the discussion in English about Boulez's aesthetic legacy. His goal in Leçons de musique is to express his conception of musical language, laid out over the course of nearly twenty years of lecturing. He is thinking about the possible paths musical thought could take, as well as the musical legacy of the pastIn addition to composers, music historians, theorists, and music students, this book will be invaluable to those interested in the history and aesthetics of 20th century music, musical manifestations of artistic modernism, the history of ideas, and French intellectual and cultural history. Faber have been Pierre Boulez's publisher since 1986 - previous books include Orientations, Boulez on Music Today and Boulez on Conducting.'Boulez's achievements in changing every part of the fabric of classical musical culture all over the world are indelible.' Tom Service, Guardian
Keywords: Composing